Psychoanalysis of Billy Hope’s Id, Ego, Superego, and Defense Mechanisms in Southpaw Movie - Simarmata, Andriyani; Syafitri, Dewi; Fiani, Ani (EDULIA: English Education, Linguistic and Art Journal, 2025)
This study aimed to analyze the id, ego, superego in the character of Billy Hope and defense mechanisms to help him deal with his trauma and influence his decision in the Southpaw Movie. The method used was descriptive qualitative. The subject of this study was Billy Hope as the main character. The data collection technique was carried out watching the movie, taking notes, and classifying the theories based on Sigmund Freud and Anna Freud. The data analysis techniques used were organizing the data, reading the data, coding, identifying themes, and representing descriptions and themes. The results showed that Billy’s id was more dominant than the ego and superego. The defense mechanisms used more were displacement/Sublimation, followed by undoing, turning against self, isolation, reaction formation, repression, and projection. The conclusion of this study were that the dominance of the id caused many of Billy Hope’s actions to arise from emotional impulses, while defense mechanisms helped him channel those emotions into action that allowed him to survive, recover from trauma, and develop into a stronger person.   Keywords: Defense Mechanisms, Movie, Psychoanalysis, Structure of the Mind.